Achieving Public Information Transparency in The Dissemination of Local Regulations - Rofi Wahanisa; Benny Riyanto; Septhian Eka Adiyatma; Uche Nnawulezi; Muhammad Abdul Rouf (Universitas Airlangga, 2023)
Comparing the disclosure of public information regarding the dissemination and publication to the public of newly enacted rules, setting Indonesia and the Netherlands as parameters is interesting as the legal cultures of both countries are intertwined and legal perspectives are constantly evolving. Despite differences in the rule of law, both countries have similar regulatory frameworks. This research uses a normative juridical writing method with a literature study to analyze the relationship between good governance and public information disclosure, including definitions, indicators, objectives, and important factors that influence the concept. The aim is to serve as a comparison parameter for a more efficient information disclosure mechanism. In Indonesia, the role of DPRDs is closely related to the issue of public information disclosure, as DPRDs have a dominant role in authority. Meanwhile, in the Netherlands, the local government takes the lead in setting regulations. Nonetheless, both countries emphasize the importance of checks and balances through the establishment of RvD and KIP, to oversee and integrate the aspirations of the community. The results of this study suggest that public information disclosure is important in both Indonesia and the Netherlands, as demonstrated by regulations that prioritize transparency, accountability, public participation, responsiveness, and the rule of law in governance. This commitment to openness aims to bridge the gap between public expectations and government actions. And in conclusion, the harmony between the process of forming regulations involving the DPRD as a representative of the people's voice and information disclosure is interrelated in public services towards the achievement of good governance.